Government Health Expenditure, Economic Growth, and Regional Development Differences—Analysis Based on a Non-parametric Additive Model - Wang, Yuxiao; Tao, Chunhai; Xiong, Qizhe (Frontiers in Public Health, 2022)
Government health expenditure plays an important role in guaranteeing people’s livelihood and in improving the quality of human capital, and it also plays an important role in affecting economic development. This paper uses a nonparametric additive model to analyze the impact of government health expenditure on economic development and regional development differences based on three aspects: linear, nonlinear and comprehensive effects. From the perspective of linear effects, the results show that the proportion of government health expenditure to GDP nationwide and in the western regions has a positive impact on economic development, while the impact in the eastern and central regions is negative. From the perspective of nonlinear effects, in the national and in the eastern, central and western regions, the proportion of government health expenditure to GDP has a significant nonlinear impact on economic development. From the perspective of comprehensive effects, the proportion of government health expenditure to GDP has a significant nonlinear positive effect on economic development nationwide and in all regions. In addition, the proportion of fixed assets investment to GDP, the proportion of exports to GDP, and the proportion of residents’ income to GDP promote nonlinear effects to different extents of non-linear promotion, but there are slight differences in different regions. Based on these estimation results, the final policy recommendations are given.